2012
DOI: 10.1177/0034355212439898
|View full text |Cite
|
Sign up to set email alerts
|

Motivational and Volitional Variables Associated With Stages of Change for Exercise in Multiple Sclerosis

Abstract: The main objective of this study was to determine whether motivational and volitional variables identified in the health action process approach (HAPA) model can be used to successfully differentiate people with multiple sclerosis (MS) in different stages of change for exercise and physical activity. Ex-post-facto design using multiple discriminant analysis was used. Participants were 215 individuals with MS. The outcome variable was measured by the Physical Activity Stages of Change Instrument, along with mot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2012
2012
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 30 publications
3
10
0
Order By: Relevance
“…He scored very highly on self-efficacy and was in the maintenance stage both for regular PA and choosing to think positively. In combination, these findings are consistent with research by Chiu et al (2012), showing individuals with MS in a more advanced stage of change for PA had higher levels of self-efficacy. Norman's case also shows that high self-efficacy may present itself in a maintenance stage of change for PA, as well as the action stage examined by Chiu et al (2012).…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…He scored very highly on self-efficacy and was in the maintenance stage both for regular PA and choosing to think positively. In combination, these findings are consistent with research by Chiu et al (2012), showing individuals with MS in a more advanced stage of change for PA had higher levels of self-efficacy. Norman's case also shows that high self-efficacy may present itself in a maintenance stage of change for PA, as well as the action stage examined by Chiu et al (2012).…”
Section: Discussionsupporting
confidence: 88%
“…In combination, these findings are consistent with research by Chiu et al (2012), showing individuals with MS in a more advanced stage of change for PA had higher levels of self-efficacy. Norman's case also shows that high self-efficacy may present itself in a maintenance stage of change for PA, as well as the action stage examined by Chiu et al (2012). Physiotherapists may consider assessing self-efficacy for both PA and wider contexts, using tools such as the MSSS.…”
Section: Discussionsupporting
confidence: 88%
“…A corollary of this theory is that an individual's stage of change is an important reflection of their readiness to exercise when they have MS, as per the transtheoretical model (Prochaska, 1979). Chiu et al (2012) found that people with MS in the action stage of change for PA have higher selfefficacy and outcome expectancy than those in a contemplative or pre-contemplative stage, but the role of positive thinking was not examined in their study. Hence, there is a need to explore whether positive thinking also distinguishes people in the stages of change and whether positive thinking could promote a more active stage of change for PA.…”
Section: Introductionmentioning
confidence: 92%
“…In contrast, either the 9-item or 6-item Control subscale was correlated equally strongly with the EXSE and SPS. Social support has been regarded as an important mediator and moderator in the adjustment mechanism of coping with MS [14][15][16][17][18]42,43], but also as a resource to build and maintain selfefficacy [7]. For instance, Bandura postulated four resources to develop an individual's self-efficacy, which are previous mastery experience (e.g.…”
Section: Construct Validitymentioning
confidence: 99%